Tradition and innovation of Albert Einstein’s villa in Caputh - Widera, Barbara (Tradycja i nowatorstwo willi Alberta Einsteina w Caputh, 2023)
The aim of the article is to analyse Albert Einstein’s villa in Caputh (1929) designed by Konrad Wachsmann in the context of the theory and history of contemporary architecture, including aspects of tradition and modernity in the adopted aesthetic, functional and spatial solutions. The research was carried out in two stages. In the first stage, based on a literature review and in situ analyses, the main features of the building were determined against the background of the functional and aesthetic tendencies prevailing during the period of the building’s construction. This allowed us to determine to what extent the design of Einstein’s villa referred to the building traditions of the region and which features reflected an innovative way of thinking, anticipating modernism in architecture. In the second part of the research, the building was characterized in the light of the latest trends in the theory and history of contemporary architecture, taking into account the principles of sustainable development, resilience of the built environment to climate change, circularity, bioclimatic design and the New European Bauhaus. The main conclusions from the conducted research concern the compromise and balance between the aspects of tradition and modernity in the Einstein’s villa, manifested in the choice of the location and adopted functional and structural solutions. The applied connection system enabling quick assembly of the building represents a very early example of prefabrication. Important innovative features include: the way of shaping the space, the use of wood as the main building material, the creation of viewing axes and the use of daylight to modulate the interiors’ ambience.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2023, nr 3 (75), s. 27-38
Keywords: architektura; modern architecture; prefabrication; circular economy; bioclimatic architecture; sustainable architecture; New European Bauhaus; architektura nowoczesna; prefabrykacja; gospodarka cyrkularna; architektura bioklimatyczna; architektura zrównoważona; Nowy Europejski Bauhaus